Dropping, Prominence and Inoperative Modern Civilization: A Study on Emily St. John Mandel’s Station Eleven - Mitriya, Nila (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
This article explores the decline of civilization and how the world changed after a collapse. It makes clear what civilization was like before the flu and how it was after the flu. A deadly disease called the Georgia flu spread rapidly and quickly wiped-out millions of people. No one has come forward to develop the civilization because everyone ran to save their lives. Thus, the development of the civilization was affected. Twenty years later, the technology of the developed world is gone. Devices, materials and technologies that seemed ordinary are seen as miraculous after the collapse. It also describes how people regret the importance of technology after its demise. It took many years for civilization to develop but it can be seen that development was destroyed by the flu within a week. There are benefits and drawbacks in civilization. No matter what civilization develops, it could not save humans from an invisible disease in the end. Thus, the paper also depicts the inoperativeness of modern civilization.